Assessment of vitamin compositions and cholesterol levels of carp (Cyprinus carpio carpio) and rainbow trout (Oncorhynchus mykiss) caviars - Inanli, Ayse Gurel; Coban, Ozlem Emir; Yilmaz, Okkes; Ozpolat, Emine; Kuzgun, Nermin Karaton (Ege Univ, Fac Fisheries, 2019)
In this study, roes obtained from carp (Cyprinus carpio carpio) that were caught from Keban Dam Lake (Elazig) and the cultured rainbow trout (Oncorhynchus mykiss) were processed as caviar and compositions of proximate and vitamins, cholesterol levels were determined in the products. In the research, roes obtained from mature fish were processed under aseptic conditions by suitable procedures for different fish species. The obtained caviars were weighed as 75 grams and filled in 200 ml capped glass jar and stored in +4 degrees C for 28 days.As a result of the analysis in the study, the amount of dry matter was determined to be 35.94% in roes obtained from rainbow trout and 31.28% in roes obtained from carp. The average protein content in raw roe obtained from rainbow trout was determined to be 24.32%, it was determined to be 18.25 % in carp. In this study, the fat content in roes obtained from rainbow trout was determined to be 9.14%, but it did not show much change during processing and it was determined to be 8.84% in the end product. During the production and storage of the caviar produced from rainbow trout and carp, the fat-soluble vitamin composition and cholesterol levels were determined. During the study, it was found that the amounts of vitamin A between rainbow trout and carp caviars were significantly different (p < 0.001). Vitamins D and K were not detected in the caviar samples. As a result of analyzes, cholesterol levels were determined 73.76 mg/100 g in rainbow trout roe and 10.82 mg/100 g in carp roe and it was observed that these values were not changed significantly during the processing and storage periods (on 0th, 7th, 14th, 21st and 28th days).
Keywords: Caviar; proximate composition; cholesterol; vitamin